De facto power of elites and regional growth. Issue 1 (11th August 2020) - Chung, Seung‐hun; Partridge, Mark D.
Abstract: Institutions are considered one of the fundamental elements of economic growth. We analyse the impact of the feudal landlordship institution on regional economic growth in nineteenth century Prussia in order to help draw implications for the modern roles of institutions. To measure landlord power, we use three measures of feudal landlordship: landowner concentration, servant population share, and household‐servant population share. These proxies, measured in 1816, are associated with both faster regional population growth and agricultural productivity growth, but no impact on industrialization in the early nineteenth century. However, in the latter nineteenth century, these same proxies are associated with delayed industrialization and no influence on regional population. Thus, stronger feudal landlordship was beneficial to regional growth when agriculture was the dominant industry but became detrimental to growth when manufacturing became dominant. Resumen: Las instituciones se consideran uno de los elementos fundamentales del crecimiento económico. Se analizó el impacto de la institución de los terratenientes feudales en el crecimiento económico regional de la Prusia del siglo XIX, a fin de contribuir a extraer consecuencias útiles para las funciones modernas de las instituciones. Para medir el poder de los terratenientes, se utilizaron tres medidas de la propiedad feudal: la concentración de terratenientes, la proporción de la población de siervos y la proporción de la población de sirvientes domésticos. Estos indicadores indirectos, medidos en 1816, están asociados tanto con un crecimiento más rápido de la población regional como con el aumento de la productividad agrícola, pero no tuvieron ningún efecto en la industrialización de principios del siglo XIX. Sin embargo, a finales del siglo XIX, estos mismos indicadores indirectos se asocian con una industrialización tardía y no influyen en la población regional. Así pues, el fortalecimiento de la propiedad feudal fue beneficioso para el crecimiento regional cuando la agricultura era la industria dominante, pero se volvió un impedimento para el crecimiento cuando la industria manufacturera se volvió dominante. 抄録: 制度は経済成長の基本的な要素の一つと考えられている。本稿では、19世紀プロイセンにおける地域の経済成長に対する封建的土地所有制度の影響を分析し、現代における制度の役割の意義を引き出す。封建的土地所有の3つの尺度(土地所有者の集中度、使用人の人口比率、家事使用人の人口比率)を使用して地主の権力を測定した。これらの代替指標は、1816年に測定されたもので、早い地域の人口増加と農業生産性の増加の両方と関連しているが、19世紀初頭の工業化に対する影響は認められない。しかし、19世紀後半には、これらの代替指標は工業化の遅れと関連しており、地域の人口に対する影響は認められない。以上のように、農業が支配的産業であった時代には、強固な封建的土地所有制度は地域の成長にとって有益であったが、製造業が支配的になると成長に対して不利益をもたらした。